This I Believe - Gopolakrishnan, R. (Tufts Archival Research Center, 2006)
R.Gopolakrishnan describes his awareness, upon coming to America, that the beliefs and dreams of Americans are the same as those of the people of India and that the desire for peace, liberty, brotherhood and cooperation are not limited by national borders.